A Study of CO2 Thermodynamic Adsorption and Desorption with Bi-Metal Loading on Zeolite Y. (2019) - Saisuwansiri, Peeradaphan; Worathanakul, Patcharin
Abstract: The increasing of carbon dioxide (CO2 ) concentration has caused high temperatures in the atmosphere. One of the major causes of CO2 comes from the combustion process of industries. Therefore, this research was to study the optimum conditions for CO2 adsorption with Cu and Fe loading on NaY zeolite. NaY zeolite was successfully synthesized using bagasse ash as the silica source. The results showed that 5.5wt%Cu-1wt%Fe/Zeolite Y impregnated to NaY (Bi-Metal loading) was suitable for CO2 adsorption. The temperature range between of 50-600 °C with 70% N2 and without N2 feed streams were studied. At 50 °C low temperature without N2 feedstream CO2 adsorption was found to be the the highest at 63.19%. Moreover, mix gas with 70% N2 and 30% CO2 at 50 °C, 5.5wt%Cu-1wt%Fe/Zeolite Y can reach 74.31% CO2 adsorption. CO2 bonding was found on zeolite after CO2 adsorption from FTIR results. TGA results demonstrated that the zeolite can be reused and it has the same CO2 conversion with the first testing.